IMPACT OF SESAME HULLS ON GROWTH AND BLOOD PROFILE IN AWASSI LAMBS - Obeidat, Belal; Shdaifat, Mustafa; Aloueedat, Mohammad; Alyahya, Linda (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The objective of this study was to evaluate the effect of dietary sesame hulls (SH) on the growth and blood profiles of growing lambs. Twenty-four lambs (initial body weight = 21.8 ± 1.35 kg; age = 75 ± 2.5 days) were randomly assigned to 3 diets. Diets with no SH (CON), 75 g/kg SH (SH75), or 150 g/kg SH (SH150), for 120 days, with 10 days adaptation period, followed by 110 days for data collection. The dry matter, crude protein, neutral detergent fiber, acid detergent fiber, and metabolizable energy intake were greater in the SH75 and SH150 diets than in the CON diet. Conversely, the group SH150 exhibited the highest values (P < 0.05) of ether extract intake. Lambs fed diets containing SH showed greater final body weight, total gain, and average daily gain than those fed the CON diet. Notably, the gain cost was lower for the SH75 and SH150 groups than for the CON diet. Blood parameters did not vary in response to the SH supplementation. Sesame hulls could be an alternative nutritional feed ingredient for growing lambs due to their nutritional value and cost-effectiveness.